2021
DOI: 10.1089/lgbt.2021.0009
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities Among Lesbian, Gay, Bisexual, Transgender, and Nonbinary Adults 50 Years Old and Older in the United States

Abstract: Purpose: The purpose of this study was to examine health disparities among LGBT and nonbinary adult subgroups of those 50 years old and older. Methods: This was a cross-sectional analysis of data from the 2019 Behavioral Risk Factor Surveillance System survey. Access to health care, disabilities, health risk and healthy behaviors, and general health and chronic diseases and conditions were compared between gay men, bisexual men, lesbian/gay women, bisexual women, transgender women, transgender men, and nonbina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Finally, most of the sample was made up of gay men (83.3%) and only a small proportion was bisexual (16.7%). Research has found that bisexual men may be at elevated risk for health disparities and shortage of social resources compared with gay men [87,88]. Although no differences were found in loneliness between the two samples, further study is needed to examine whether the role of loneliness in health differs between gay and bisexual men.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, most of the sample was made up of gay men (83.3%) and only a small proportion was bisexual (16.7%). Research has found that bisexual men may be at elevated risk for health disparities and shortage of social resources compared with gay men [87,88]. Although no differences were found in loneliness between the two samples, further study is needed to examine whether the role of loneliness in health differs between gay and bisexual men.…”
Section: Discussionmentioning
confidence: 91%
“…Second, since our administrative data did not capture gender identity, we were forced to infer the gender identity of our sample and combine individuals who likely hold nonbinary and binary gender identities in the same category based on their shared use of certain gender-affirming hormones, procedures, or anatomy-specific care. Nonbinary transgender people have been shown to have differential healthcare utilization and risk of various health outcomes than binary transgender people ( 32 , 120 ), and so the necessary combining of these groups in the present study may have obscured key differences in the probability of being diagnosed with one or more health conditions. Third, transgender and cisgender beneficiaries were included in our study based on their observed care, whereas individuals who did not access relevant care through fee-for-service Medicare at any point during the study period were not included; thus, our sample is unlikely to represent all aging transgender and cisgender Medicare beneficiaries.…”
Section: Discussionmentioning
confidence: 97%
“…Extending prior research ( 3 , 5 , 12 , 13 , 30 , 31 , 33 ), we observed an elevated burden of health condition diagnoses among TFN or TMN people overall, with the greatest burden observed among TFN people relative to other groups. Our novel methods to identify a transgender sample using Medicare claims data and infer gender may be helpful for future researchers seeking to study the diagnosis of rare conditions, as well as identify transgender subgroups in need of preventive and treatment interventions aimed at reducing morbidity ( 26 , 29 , 30 , 32 ) and mortality ( 42 , 121 ) among aging transgender people in the U.S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the number of participants who identified as transgender or gender non-binary was small. We could not conduct analyses to determine differences in outcomes between cisgender and transgender/non-binary participants even though research has shown differences in mental health outcomes between subsets of the SGM community [ 68 ].…”
Section: Discussionmentioning
confidence: 99%